The Disparity in Criminal Prosecution against Acid Attack on Investigator of Corruption Eradication Commission: "Novel Baswedan” Case - Riyadi, Bambang Slamet; Usman; Sudarti, Elly (International Journal of Criminology and Sociology, 2022)
This study aims to analyze the causes of the disparity in the criminal prosecution against acid attack. It is suspected that there has been a conspiracy of abuse of power between investigators and prosecutors, which reflects injustice in the criminal procedure law. This research clarifies a case study of the disparity of prosecution through mutually acknowledged norms and values. Case studies also enable the researchers to study the real thing, and gain a better understanding of what disparities in criminal prosecution. The result of the research showed that it was suspected that there had been a conspiracy of abuse of power between the investigator and the prosecutor, so that there was no justice for the victim. The researchers suggest limiting the prosecutors ’discretion and the existence of an independent institution for prosecutors’ supervisory functions.